The role of mononuclear phagocyte system in IgA nephropathy: pathogenesis and prognosis - Liu, Yiwen; Gong, Yan; Xu, Gaosi (Frontiers in Immunology, 2023)
Although the “multiple hits” theory is a widely accepted pathogenesis in IgA nephropathy (IgAN), increasing evidence suggests that the mononuclear/macrophage system plays important roles in the progression of IgAN; however, the exact mechanism is unclear. In the present study, we explored 1,067 patients in 15 studies and found that the number of macrophages per glomerulus was positively related with the degree of hematuria, and the macrophages in the glomeruli were mainly related to mesangial proliferation (M) in renal biopsy. In the tubulointerstitium, macrophages were significantly paralleled to tubulointerstitial α-SMA and NF-kB expression, tubulointerstitial lesion, tubule atrophy/interstitial fibrosis (T), and segmental glomerulosclerosis (S). In the glomeruli and tubulointerstitium, M1 accounted for 85.41% in the M classification according to the Oxford MEST-C, while in the blood, M1 accounted for 100%, and the patients with low CD89+ monocyte mean fluorescence intensity displayed more severe pathological characteristics (S1 and T1-2) and clinical symptoms. M1 (CD80+) macrophages were associated with proinflammation in the acute phase; however, M2 (CD163+) macrophages participated in tissue repair and remodeling, which correlated with chronic inflammation. In the glomeruli, M2 macrophages activated glomerular matrix expansion by secreting cytokines such as IL-10 and tumor necrosis factor-β (TGF-β), and M0 (CD68+) macrophages stimulated glomerular hypercellularity. In the tubulointerstitium, M2 macrophages played pivotal roles in renal fibrosis and sclerosis. It is assumed that macrophages acted as antigen-presenting cells to activate T cells and released diverse cytokines to stimulate an inflammatory response. Macrophages infiltrating glomeruli destroy the integrity of podocytes through the mesangio-podocytic-tubular crosstalk as well as the injury of the tubule.